Mediational role of parenting styles in emotional intelligence of parents and aggression among adolescents. (20th November 2014) - Batool, Syeda Shahida; Bond, Rod
<x xml:space="preserve">Abstract</x> The present study was designed to examine the relationship between parents' emotional intelligence and adolescents' aggression, through the mediation of parenting styles. Two hundred and twenty five undergraduate students (113 boys & 112 girls; age 17–18 years), from four universities in Pakistan, participated with their parents. The Parenting Styles and Dimensions Questionnaire (Robinson, Mandleco, Olsen, & Hart, 1995), and the Scale of Emotional Intelligence (Batool & Khalid, 2011) were completed by parents. The Aggression Questionnaire (Buss & Perry, 1992) was completed by their adolescent offspring. Mediational path analysis supported our hypothesised model. Results indicate that emotional intelligence of parents indirectly links to aggression among offspring, through parenting styles. It was concluded that emotional intelligence training will help parents to improve their parenting styles, and it will lower the risk of aggression in their children.